(untitled) (Advances in Civil and Architectural Engineering, 2021)
Structuring a project team is highly sensitive task, so numerous methods which address the problem have emerged. One of the most effective methods is structuring teams by the team members’ affinities and talents presented as team roles. In this paper, we applied Belbin’s Self-Perception Inventory in order to investigate the following questions: Which are the most engaged team roles? How does the absence of the most engaged team members affect the team’s efficiency? How does this change of the team environment affect the member? Our results show that, even in small project teams, changes in team structure will surely have a negative effect on the team’s organizational culture in a short run, and even more importantly they decrease the team’s overall productivity. Also, the changes had a negative effect at the individual level; teams had trouble integrating new members, and individuals had trouble integrating themselves in new teams.